Surgical Antibiotic Prophylaxis: Incidence and Risk of Surgical Site Infection - B., Fadzwani; A.R., Raha; M.N., Nadia; WM., Wan Rahiza; J., Razman; A.J, Nordiah (IIUM Medical Journal Malaysia, 2020)
Introduction: This prospective cross sectional study assessed surgical antibiotic prophylaxis (SAP) practice, the incidence of surgical site infection (SSI) and its associated risks in Universiti Kebangsaan Malaysia Medical Centre. Methods: Patients for elective colorectal, hepatobiliary, upper gastrointestinal, breast and endocrine surgery, who received SAP were included and followed up until day-30 postoperatively. Types of antibiotic, preoperative–dose timing, intraoperative re-dosing and its duration were recorded. The incidence of SSI was calculated and its associated risks expressed in odds ratio. Results: Out of 166 patients recruited, 121 (72.89%) patients received SAP preoperatively, and 91 (75.21%) of them were prescribed the appropriate antibiotic as per our institutional guideline. Three patients who continued to receive therapeutic antibiotic postoperatively were excluded from statistical analysis. Eleven (9.10%) patients received SAP beyond the preoperative–dose timing of 60 minutes (p=0.001), which was an independent risk factor for SSI (adjusted OR 4.527, 95% CI; 1.058-19.367, p=0.042). The risk of SSI also remained in patients who continued to receive SAP beyond 24 hours (OR 4.667, 95% CI; 1.527-14.259, p=0.007). The overall rate of SSI was 17.18%. Conclusion: We found that the choice of antibiotic prescribed for SAP was in accordance to institutional guideline and the relatively high SSI incidence was similar to a recent local report. Although the number of patients receiving preoperative dose-timing of > 60 minutes was low, it was nonetheless an independent risk factor for SSI. The postoperative continuation of SAP for more than 24 hours showed no benefit in reducing SSI.